Doing what with whom? Stakeholder analysis in a large transdisciplinary research project in South-East Asia - Spangenberg, Joachim H.; Heong, K.L.; Klotzbücher, Anika; Klotzbücher, Thimo; Nguyen, Quynh Anh; Tekken, Vera; Truong, Dao Thanh; Türke, Manfred; Settele, Josef (Springer, 2018)
The transdisciplinary research project LEGATO analysed the combined generation of provisioning, regulating and cultural ecosystem services in wet rice agriculture in South-East Asia and applied ecological engineering to future-proof it against global change and environmental pollution challenges. Due to its transdisciplinary character and the sheer size, a systematic stakeholder involvement was inevitable. Starting with stakeholder identification by snowballing from a limited number of contacts, we derived a multi-level stakeholder analysis and tried to involve those identified as relevant. Applying different means and aiming at different depth of involvement, the effort can be judged successful. The paper describes the methods used to identify and classify stakeholders, and key elements of the stakeholder management, guided by the BiodivERsA Stakeholder Activation Handbook. While on the local level, farmers and extension workers turned out to be influential and interested stakeholders in both countries, as well as local (PH) or provincial authorities (VN), differences were manifest on higher levels due to the divergent institutional setting. National-level agents were hard to get interested in both countries, and influential agents along the production chain, including middle men, were not really interested in collaboration